1976
DOI: 10.1104/pp.58.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of Anthocyanin Synthesis

Abstract: (2,4,6,7,9,12,18) and it has also been suggested that phytochrome may be the only photoreceptor involved, at least for HIR responses in the FR region (2,7,10,12,18). However, it has not been definitely proved that phytochrome is the only HIR photoreceptor and it has been suggested that other photoreactive systems may play a role in HIR responses (4,(13)(14)(15). There is some evidence for a contribution of photosynthesis to the synthesis of anthocyanins in green systems which have a functional photosynthetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In a previous note (10), we suggested that the reciprocity failure of the HIR could be explained in terms of phytochrome, and that the irradiance dependence perhaps was no more than (8,10), the fact that phytochrome was involved in the photocontrol of anthocyanin production under inductive conditions (8,9), and some ancillary observations (9,11,12) strongly suggested that the photoreceptor was phytochrome.…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…In a previous note (10), we suggested that the reciprocity failure of the HIR could be explained in terms of phytochrome, and that the irradiance dependence perhaps was no more than (8,10), the fact that phytochrome was involved in the photocontrol of anthocyanin production under inductive conditions (8,9), and some ancillary observations (9,11,12) strongly suggested that the photoreceptor was phytochrome.…”
mentioning
confidence: 81%
“…The light treatments were started 96 hr after sowing and were given in growth chambers equipped with the light sources described in previous papers (8)(9)(10)(11)(12). Temperature between the A657 values of the acidic methanol extracts and the Chl content of the seedlings (12). The volume of the extracts was either 15 ml (Figs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations